A Case Report of a 70-Year-Old Male with Chronic Thromboembolic Pulmonary Hypertension (CTEPH), when to be aware? - Chaifung Carolline; Siahaan, Sylvia Sagita; Widysanto, Allen; Wahyuni, Titis Dewi; Wijaya, Victor Nugroho; Sirait, Magdalena; Pradono, Clarissa Moira (Malang Respiratory Journal, 2026)
Background Chronic thromboembolic pulmonary hypertension (CTEPH) is an uncommon disorder that arises as a complication of unresolved pulmonary embolism (PE). Without timely intervention, it poses a substantial risk of increased morbidity and mortality. Case A 70-year-old male was admitted with complaints of shortness of breath and productive cough that had persisted for three days prior to hospitalization. He reported progressive exertional dyspnea over the past six months. On examination, the patient exhibited refractory hypoxemia and jugular venous distention. Diagnostic imaging, including computed tomography pulmonary angiography (CTPA) and a lung perfusion scan, confirmed a diagnosis of CTEPH. Laboratory results revealed an elevated D-dimer level of 18.27 mg/dL. The patient was treated with subcutaneous anticoagulants and oral anticoagulant therapy, resulting in clinical improvement. Upon discharge, he was prescribed pulmonary vasodilators and lifelong anticoagulation therapy to maintain his condition. Conclusion Pulmonary vascular disease should be considered as a differential diagnosis in patients with unexplained dyspnea. CTPA is recommended as a diagnostic modality for confirming CTEPH. Lifelong anticoagulation is essential in managing CTEPH, with the primary treatment goals being the restoration of normal pulmonary blood flow, reducing the workload on the right ventricle, and preventing or addressing small vessel disease. Keywords chronic thromboembolic pulmonary hypertension, oral anticoagulant, Computed Tomography Pulmonary Angiography